Automated microfluidic synthesis of N-succinimidyl 4-[18F] fluorobenzoate: a protein labelling agent - Tutar, Rumeysa (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Describes automated microfluidic synthesis of a radiofluorinated labeling agent for PET imaging. Protocol achieves good radiochemical purity and yield, with successful application to blood pool imaging agent synthesis.